PENINGKATAN SIKAP MANDIRI DAN HASIL BELAJAR MATERI MAKNA PANCASILA MENGGUNAKAN PENDEKATAN KONTEKSTUAL SISWA KELAS IV SDK GAMPING - Aldy, Lukas; Purnomo, Puji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of independence and learning outcomes of fourth-grade students at Kanisius Gamping Elementary School in the 2025/2026 academic year. These conditions were identified through observation, interviews, and questionnaires completed by fourth-grade students at Kanisius Gamping Elementary School. This study aims to improve the independence and learning outcomes of fourth-grade students at Kanisius Gamping Elementary School through the application of a contextual approach. This research is a classroom action research (CAR). The research subjects are fourth-grade students at Kanisius Gamping Elementary School in the 2025/2026 academic year. This research uses data collection techniques through observation, questionnaires, interviews, and learning outcome tests. The data analysis technique used is quantitative descriptive. The results of the study show that: 1) The application of a contextual approach through the components of constructivism, inquiry, learning community, questioning, modeling, reflection, and authentic assessment was able to improve students' independence and learning outcomes in the subject of Pancasila; 2) The application of the contextual approach was able to improve students' independent attitudes, with an average initial score of 48.78, increasing to 60.24 in cycle I, and increasing in cycle II to 78.71; 3) The application of a contextual approach can improve student learning outcomes, as seen in the average initial score of 59.07 with a mastery level of 28.57%, increasing to 65.71 with a mastery level of 50.00% in cycle I, and increasing to 82.61 with a mastery level of 85.71% in cycle II; 4) The contextual approach was effective in improving students' independent attitudes and learning outcomes, as indicated by an N-Gain Score for independent attitudes of 0.5 in the “moderate” category with an effectiveness percentage of 59% and in the “quite effective” category. In addition, the improvement in student learning outcomes is shown by an N-Gain Score of 0.6 in the “moderate” category with an effectiveness percentage of 63% and in the “quite effective” category. Keywords: Contextual Approach, Independent Attitude, Learning Outcomes